Pengenaan Pajak Penghasilan Untuk Usaha Mikro, Kecil Dan Menengah (UMKM) Di Indonesia - Setiadi Alim Lim; Lilik Indrawati (BIP's JURNAL BISNIS PERSPEKTIF, 2014)
Groups of micro, small and medium enterprises (MSMEs) in many countries are generally low in having the level of compliance to pay taxes. The high level of non-compliance, among others due to the high compliance costs to be incurred by MSMEs to meet their tax obligations through the tax system standards applied by a country. To overcome this, many countries generally use a simpler tax system or MSMEs and are known as the presumptive tax system. In addition, given the arge role of MSMEs to the national economy of a country, MSMEs are often given tax breaks and incentives. This paper aims to carry out a theoretical study of the application of the tax system applied to MSMEs in Indonesia.